Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The Euler-Mascheroni constant gamma is defined as:

$$\gamma=\lim\limits_{n \rightarrow \infty}\left(\sum\limits_{m=1}^{n} \frac{1}{m} - \log(n)\right)$$

From this previous question Do these series converge to logarithms? $\log(n)$ can be written:

$$\log(n)=\sum\limits_{k=1}^\infty \sum\limits_{a=1}^{n-1}\frac{1}{kn-a}-\sum\limits_{k=1}^\infty\frac{n-1}{kn}$$

$$\gamma=\lim\limits_{n \rightarrow \infty}\left(\sum\limits_{m=1}^{n} \frac{1}{m} - \left(\sum\limits_{k=1}^\infty \sum\limits_{a=1}^{n-1}\frac{1}{kn-a}-\sum\limits_{k=1}^\infty\frac{n-1}{kn}\right)\right)$$

$$\gamma=\lim\limits_{n \rightarrow \infty}\left(\sum\limits_{m=1}^{n} \frac{1}{m} - \sum\limits_{k=1}^\infty \sum\limits_{a=1}^{n-1}\frac{1}{kn-a} + \sum\limits_{k=1}^\infty\frac{n-1}{kn}\right)$$

Can this last expression be further simplified?

share|cite|improve this question
Perhaps it is not good to have a divergent series like $\sum\limits_{k=1}^\infty\frac{n-1}{kn}$ inside your formula. – GEdgar Jun 21 '11 at 15:17
That is, you want $$\log(n)=\sum\limits_{k=1}^\infty \left[\sum\limits_{a=1}^{n-1}\frac{1}{kn-a}-\frac{n-1}{kn}\right]$$ not two separate sums. – GEdgar Jun 21 '11 at 15:32
@GEdgar: That is probably right. – Mats Granvik Jun 21 '11 at 16:28
up vote 10 down vote accepted

Careful, we don't actually have

$$\log(n)=\sum\limits _{k=1}^{\infty}\sum\limits _{a=1}^{n-1}\frac{1}{kn-a}-\sum\limits _{k=1}^{\infty}\frac{n-1}{kn},$$

since neither series converges. Instead we have

$$\log(n)=\lim_{M\rightarrow\infty}\sum\limits _{k=1}^{M}\sum\limits _{a=1}^{n-1}\frac{1}{kn-a}-\sum\limits _{k=1}^{M}\frac{n-1}{kn}.$$

Now, since

$$\sum\limits _{k=1}^{M}\frac{n-1}{kn}=\sum\limits _{k=1}^{M}\frac{1}{k}-\sum\limits _{k=1}^{M}\frac{1}{kn}$$

we can rewrite

$$\log(n)=\lim_{M\rightarrow\infty}\sum\limits _{k=1}^{M}\sum\limits _{a=0}^{n-1}\frac{1}{kn-a}-\sum\limits _{k=1}^{M}\frac{1}{k}=\lim_{M\rightarrow\infty}\sum_{k=1}^{nM}\frac{1}{k}-\sum_{k=1}^{M}\frac{1}{k}.$$

Thus we have


Personally, I quite like this limit since it has a nice symmetry when we switch the order of the limits. Also, it generalizes to give limits over l variables which are invariant under permutation. Let $H_{k}$ be the $k^{th}$ harmonic number. Then the above was


Here is $l=3$:


In general

$$\gamma=\lim_{n_{1}\rightarrow\infty}\cdots\lim_{n_{l}\rightarrow\infty}\left(\sum_{i_{1}=1}^{l}H_{n_{i_{1}}}-\sum_{i_{1}<i_{2}\leq l}H_{n_{i_{1}}n_{i_{2}}}+\cdots+(-1)^{l}H_{n_{1}\cdots n_{l}}\right).$$

So I guess it depends on what you mean by “simplify further.” I find the form


to be quite simple.

Hope that helps,

share|cite|improve this answer
Wow thanks, that is a really nice looking expression in the middle of your answer after "Thus we have". If I understood it right, the use of a double limit is the way to make it computable. My choice of words was not so good. I should have left out the word "further". – Mats Granvik Jun 21 '11 at 16:20
Does:$$\lim_{n_1\to\infty}\lim_{n_2\to\infty}\lim_{n_3\to\infty}\frac12(H_{n_1}+‌​H_{n_2}+H_{n_3}-H_{n_1n_2n_3})$$also equal $\gamma$? – Akiva Weinberger Jan 26 at 20:21
Yeah, it does, because that's equal to:$$\lim_{n_1\to\infty}\lim_{n_2\to\infty}\lim_{n_3\to\infty}\\ \frac12\big((H_{n_1}-\ln n_1)+(H_{n_2}-\ln n_2)+(H_{n_3}-\ln n_3)-(H_{n_1n_2n_3}-\ln n_1n_2n_3)\big)$$which goes to $\frac12(\gamma+\gamma+\gamma-\gamma)=\gamma$. Same strategy proves the similar limits in the answer. – Akiva Weinberger Jan 26 at 20:29

@Eric can you give the proof that this is equal (for every possible value of n): $$\ln(n)=\lim_{M\rightarrow\infty}\sum\limits _{k=1}^{M}\sum\limits _{a=1}^{n-1}\frac{1}{kn-a}-\sum\limits _{k=1}^{M}\frac{n-1}{kn}.$$

share|cite|improve this answer

Setting $m=n$ in Naslund's equation we get

$$ \gamma= \sum_{n=1}^\infty \left(\frac{2}{n}-\sum_{j=n(n-1)+1}^{n(n+1)} \frac{1}{j}\right) $$

This may be used to write a closed form for the digamma function, see Re-Expressing the Digamma.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.